Integrating Artificial Intelligence in a Morphology Course - An Analytical Study of University Students’ Perspective - Ayoub, Nawal Nabih; Joudi, Nadine Sami; Bou Saba, Miriama Salim; Bou Saba, Anthony Salim (European Scientific Journal, ESJ, 2024)
This paper focuses on scrutinizing the attitudes and opinions of English as Foreign Language (EFL) learners on the integration of artificial intelligence (AI) in a morphology course in higher education in Lebanon. Specifically, it examines AI as a pedagogical tool in classrooms to provide learners with personalized learning paths centered on their needs and strengths, offer automated feedback on activities and assignments, supply study resources and extra material, furnish adaptive assessments, and most importantly, identify common errors in students’ responses that allow instructors to acknowledge the learning gaps and tailor their teaching strategies accordingly. It also aims to determine the students’ perspectives on AI’s potent role in learning. In this exploratory study, a mixed-method design and a convenient sampling of participants were utilized. A total of 62 EFL students at the public university in Lebanon participated in the study. To describe and quantify their perceptions of integrating AI in a morphology course, an online survey, including closed-ended and open-ended questions, and two focus group discussions were administered. The overall qualitative and quantitative analyses of the data indicated that Lebanese EFL students have positive attitudes towards integrating AI in a morphology course as a pedagogical tool and as a fundamental part of the teaching strategies in EFL higher education classes since it provides a good source of information and aids in the teaching and learning process. However, the findings also revealed the need to train teachers and students to use AI technologies, keeping in mind the potent role of the instructor in class.